Leadership in Action: Bridging Boundaries: Meeting the Challenge of Workplace Diversity - Ernst, Christopher; Yip, Jeffrey (Center for Creative Leadership, 2008)
In today's globally diverse and increasingly interconnected world, social identity boundaries rub together, pull apart, and collide in the workplace. When identity divides open up, people look to leaders to bridge the gaps. By employing four tactics-suspending, reframing, nesting, and weaving- leaders can facilitate positive cross-boundary interactions.